Analisis Yuridis Pemenuhan Hak Anak dalam Proses Diversi pada Putusan Nomor 10/Pid.Sus-Anak/2024/PN Unr - Davito Marco Pradipta; Nining Yurista Prawitasari (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Diversion is a mechanism for resolving juvenile criminal cases outside the formal judicial process through a restorative justice approach. This study aims to analyze the regulation of diversion under Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and the fulfillment of children's rights based on Decision Number 10/Pid.Sus-Anak/2024/PN Unr. This research employs normative legal research using statutory and case approaches. The results indicate that diversion serves as a child protection instrument, although its implementation remains constrained by legal requirements and the agreement of the parties involved. In the examined case, the child's rights were fulfilled through legal assistance, social guidance, and educational protection despite the continuation of formal judicial proceedings.